PK/PD modeling of FXI antisense oligonucleotides to bridge the dose‐FXI activity relation from healthy volunteers to end‐stage renal disease patients. (23rd June 2021) - Willmann, Stefan; Marostica, Eleonora; Snelder, Nelleke; Solms, Alexander; Jensen, Markus; Lobmeyer, Maximilian; Lensing, Anthonie W. A.; Bethune, Claudette; Morgan, Erin; Yu, Rosie Z.; Wang, Yanfeng; Jung, Shiangtung W.; et al.
Abstract: IONIS‐FXIRX (BAY2306001) is an antisense oligonucleotide that inhibits the synthesis of coagulation factor XI (FXI) and has been investigated in healthy volunteers and patients with end‐stage renal disease (ESRD). FXI‐LICA (BAY2976217) shares the same RNA sequence as IONIS‐FXIRX but contains a GalNAc‐conjugation that facilitates asialoglycoprotein receptor (ASGPR)‐mediated uptake into hepatocytes. FXI‐LICA has been studied in healthy volunteers and is currently investigated in patients with ESRD on hemodialysis. We present a model‐informed bridging approach that facilitates the extrapolation of the dose‐exposure‐FXI relationship from IONIS‐FXIRX to FXI‐LICA in patients with ESRD and, thus, supports the selection of FX‐LICA doses being investigated in patients with ESRD. A two‐compartment pharmacokinetic (PK) model, with mixed first‐ and zero‐order subcutaneous absorption and first‐order elimination, was combined with an indirect response model for the inhibitory effect on the FXI synthesis rate via an effect compartment. This PK/pharmacodynamic model adequately described the median trends, as well as the interindividual variabilities for plasma drug concentration and FXI activity in healthy volunteers of IONIS‐FXIRX and FXI‐LICA, and in patients with ESRD of IONIS‐FXIRX . The model was then used to predict dose‐dependent steady‐state FXI activity following repeat once‐monthly doses of FXI‐LICA in a virtual ESRD patient population. Under the assumption of similar ASGPR expression in patients with ESRD and healthy volunteers, doses of 40 mg, 80 mg, and 120 mg FXI‐LICA are expected to cover the target range of clinical interest for steady‐state FXI activity in the phase IIb study of FXI‐LICA in patients with ESRD undergoing hemodialysis.